The Effect of Tourism Facilities, Service Quality and Promotion of Tourist Satisfaction in South Pesisir District - Arif Mustaqim Bahar; Maizaldi Maizaldi; Novrianto Putera; Resky Widiestuty; Syafrianto Chaniago; Yulina Eliza (J-MAS (Jurnal Manajemen dan Sains), 2020)
The purpose of this study was to determine the effect of tourism facilities on tourist satisfaction in South Coastal District, to determine the effect of  service quality on tourist satisfaction in South Coastal District, to determine the effect of promotion on tourist satisfaction in South Coastal District. The method used is a quantitative research using descriptive, while the data collection used questionnaire. The sampling technique is non probability sampling with a type of purposive sampling of 115 respondents. The results of this study can be concluded that the: (1) Tourism facilities has a positive and significant effect on tourist satisfaction in South Coastal District. (2) Service quality has a positive and significant effect on tourist satisfaction in South Coastal District. (3) Promotion has a positive and significant effect on tourist satisfaction in South Coastal District.